Rheumatic Valvular Lesions: Surgical Interventions - Koirala, B; Koirala, R; Sharma, J; Pradhan, S; Acharya, A; Sharma, P; Rai, K (Nepalese Heart Journal, 2004)
This is a retrospective study of the patients with the diagnosis of Rheumatic Valvular Lesions, who had undergone surgical treatment at SGNHC between Aug 2001 and Jan 2004, The data was collected from the in-hospital records maintained for individual patient.